Interpretação e apropriação dos resultados dos processos avaliativos em rede e o uso de sistemas digitais: implementação do Índice de Desenvolvimento da Educação Paulistana - Passos, Sílvia Regina Nazaré Camilo (2022)
The objective of this paper is to analyze the large-scale assessment tests carried out by the Office Department of Education at São Paulo city and the impacts caused on the city school management by the establishment of the São Paulo Education Development Index, since 2019. That analysis can get advances and collaborate to the improvement of digital services and technological tools to meet the needs of the school network, strengthen the control on the education policies and the application of resources by management and community. It was proposed, that way, to cut out one of the initiatives of the Office Department of Education at São Paulo city, about the mechanisms of data collection of learning, from the application of external and largescale assessment. Considering the appropriate use of assessment results by school managers, the implementation of a data management system and the creation of a performance indicator can help improve the job of all in school and, consequently, the performance of students, besides proposing collective reflections that result changes in the teaching proposal, around an expanded conception of the public policies of largescale assessment, understanding the data as important information to (re)think learning strategies, involving a multidiscipline team, which can contribute, in the middle term, to students achieving the most advanced levels of proficiency. The methodology chosen was the qualitative research, through an exploratory study, having a fundamental category the large-scale assessment and the formulation of public policies. In that case, the question is based on how the appropriation and reflections on those evaluations are carried out and how the creation of a municipal indicator can contribute, throughout the educational process, for improving the quality of education in the cities, besides indicating factors that interfere in the use of those results by school managers of the cities network education. The research reveals the importance of creating increasingly complex indicators and appropriate to the reality of each site, in order to return more quickly to schools with the change of educational practices that, possibly, were not satisfactory, making possible, thus, to correct routes and identify specific interventions with a goal improving the quality of teaching, providing a great way for the (re)formulation of educational public policies in the short, middle, and long term